THE INFRASTRUCTURE COMPETITIVENESS OF NEW DEVELOPMENT TEN TOURIST DESTINATION IN INDONESIA - Hidayat, Candra (Jurnal Ilmiah Pariwisata, 2018)
In this research investigates the infrastructure competitiveness of new development ten tourist destinations performance in Indonesia. It deeply analyzes Infrastructure board organized into three pillars factors of competitiveness. First pillar is Air transporinfrastructure, second pillar is Ground and port infrastructure and third pillar is Tourisservice infrastructure. Research was made by descriptive and research was focused by using secondary data. According to the result, the rank of new development tourist destinations will be number ten is North Maluku, number nine is Southeast Sulawesi, number eight is Bangka Belitung, number seven is East Nusa Tenggara, number six is West Nusa Tenggara, number five is North Sumatra, number four is Jakarta, number three is Central Java, number two is East Java and number one is Banten.